Crustal structure of the Transantarctic Mountains, Ellsworth Mountains and Marie Byrd Land, Antarctica: constraints on shear wave velocities, Poisson's ratios and Moho depths. Issue 3 (4th August 2017) - Ramirez, C.; Nyblade, A.; Emry, E.L.; Julià, J.; Sun, X.; Anandakrishnan, S.; Wiens, D.A.; Aster, R.C.; Huerta, A.D.; Winberry, P.; Wilson, T.
Abstract: A uniform set of crustal parameters for seismic stations deployed on rock in West Antarctica and the Transantarctic Mountains (TAM) has been obtained to help elucidate similarities and differences in crustal structure within and between several tectonic blocks that make up these regions. P -wave receiver functions have been analysed using the H – κ stacking method to develop estimates of thickness and bulk Poisson's ratio for the crust, and jointly inverted with surface wave dispersion measurements to obtain depth-dependent shear wave velocity models for the crust and uppermost mantle. The results from 33 stations are reported, including three stations for which no previous results were available. The average crustal thickness is 30 ± 5 km along the TAM front, and 38 ± 2 km in the interior of the mountain range. The average Poisson's ratios for these two regions are 0.25 ± 0.03 and 0.26 ± 0.02, respectively, and they have similar average crustal Vs of 3.7 ± 0.1 km s −1 . At multiple stations within the TAM, we observe evidence for mafic layering within or at the base of the crust, which may have resulted from the Ferrar magmatic event. The Ellsworth Mountains have an average crustal thickness of 37 ± 2 km, a Poisson's ratio of 0.27, and average crustal Vs of 3.7 ± 0.1 km s −1, similar to the TAM. This similarity is consistent with interpretations of the Ellsworth Mountains as a tectonically rotated TAM block. The Ross Island region has an average Moho depth of 25 ± 1 km, an average crustal Vs of 3.6 ± 0.1 km s −1 and Poisson's ratio of 0.30, consistent with the mafic Cenozoic volcanism found there and its proximity to the Terror Rift. Marie Byrd Land has an average crustal thickness of 30 ± 2 km, Poisson's ratio of 0.25 ± 0.04 and crustal Vs of 3.7 ± 0.1 km s −1 . One station (SILY) in Marie Byrd Land is near an area of recent volcanism and deep (25–40 km) seismicity, and has a high Poisson's ratio, consistent with the presence of partial melt in the crust.